Synthesis of beta-AgVO3 nanowires by hydrothermal and precipitation routes: a comparative study - Canuto de Menezes, Beatriz Rossi; Ribas, Renata Guimaraes; Schatkoski, Vanessa Modelski; Amaral Montanheiro, Thais Larissa do; Koga-Ito, Cristiane Yumi [UNESP]; Thim, Gilmar Patrocinio (Springer, 2019)
Silver vanadate, especially beta-AgVO3, have a wide range of technological applications due to remarkable biological, optical, and electrical features. The structure, morphology, and properties of beta-AgVO3 are directly affected by synthesis conditions. A comparative study between two different synthesis routes (precipitation and hydrothermal) of beta-AgVO3 was systematically investigated in this work. X-ray diffraction, Raman spectroscopy, scanning electron microscopy, zeta potential, and UV-visible spectrometry results showed that the hydrothermal method produced more homogeneous samples of beta-AgVO3, with elevated purity and crystallinity. In addition, the sample of beta-AgVO3 obtained by hydrothermal method had a wire-like morphology while that obtained by precipitation had irregular shape. Finally, the hydrothermal procedure showed more elevated reproducibility.
Keywords: Silver vanadate; beta-AgVO3; Precipitation synthesis; Hydrothermal method